2010
DOI: 10.1111/j.1365-2559.2010.03560.x
|View full text |Cite
|
Sign up to set email alerts
|

Monocarboxylate transporter 1 is up‐regulated in basal‐like breast carcinoma

Abstract: These results provide evidence for a prognostic value of MCT1 in breast carcinoma and support the exploitation of the complex MCT1/CD147 as a promising target for cancer therapy, especially in basal-like breast carcinoma.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

10
152
3
1

Year Published

2011
2011
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 171 publications
(166 citation statements)
references
References 44 publications
10
152
3
1
Order By: Relevance
“…In this work, we analysed MCT1 and MCT4 expression, as well as the expression of other relevant proteins in cancer metabolism, in a variety of human breast cancer cell lines. MCT1 was strongly expressed at plasma membrane in MDA-MB-468, Hs578T and BT20 (basal-like subtype cells), in accordance with our findings for human breast carcinoma samples (Pinheiro et al 2010). In MDA-MB-231, also basal-like subtype cells, MCT1 was not detected, as described by others (Asada et al 2003, Gallagher et al 2007, Hussien & Brooks 2011, and the same was observed for the Her2-positive subtype cell line (SkBr3).…”
Section: Discussionsupporting
confidence: 91%
See 3 more Smart Citations
“…In this work, we analysed MCT1 and MCT4 expression, as well as the expression of other relevant proteins in cancer metabolism, in a variety of human breast cancer cell lines. MCT1 was strongly expressed at plasma membrane in MDA-MB-468, Hs578T and BT20 (basal-like subtype cells), in accordance with our findings for human breast carcinoma samples (Pinheiro et al 2010). In MDA-MB-231, also basal-like subtype cells, MCT1 was not detected, as described by others (Asada et al 2003, Gallagher et al 2007, Hussien & Brooks 2011, and the same was observed for the Her2-positive subtype cell line (SkBr3).…”
Section: Discussionsupporting
confidence: 91%
“…Recently, our group described an increase in MCT1 expression in breast carcinomas, when compared with normal tissue. This enhanced MCT1 expression, as well as the expression of CD147, a MCT1/MCT4 chaperone (Kirk et al 2000, Gallagher et al 2007, was associated with basal-like-subtype tumours and other poor prognostic parameters (Pinheiro et al 2010). Additionally, we found that MCT1, but not MCT4, was associated with GLUT1 and CAIX expressions, indicating a role of MCT1 in the hyperglycolytic and acid-resistant phenotype characteristic of less oxygenated (Pinheiro et al 2011), instead of oxygenated cancer cells as pointed by others (Sonveaux et al 2008).…”
Section: Introductionsupporting
confidence: 65%
See 2 more Smart Citations
“…In this study, LOXL-1 is suggested as a cancer metastasis-associated protein, likely correlated to cancer hypoxic status-associated metastasis. Similarly, MCT1 is significantly increased in breast carcinomas compared with normal breast tissue and, significantly, MCT1 is associated with poor prognostic variables including high-grade tumors (36). MCT1 expression is also associated with advanced gastric carcinoma and lymph node metastasis (37).…”
Section: Discussionmentioning
confidence: 99%